Bacillus thuringiensis as a feed additive to control Musca domestica associated with poultry houses - Bouthaina A. Merdan (Journal of Basic and Applied Zoology, 2012)
The bacterium Bacillus thuringiensis proved to be a good candidate in controlling Musca domestica, associated with poultry houses, as a carrier of a wide range of pathogens infecting man and animals. Chicken feces are good media attracting flies for breeding. The bacterium was used in commercial form and a laboratory preparation form to contaminate feces or administered orally to chicken. Reduction in the percentages of pupal and adult emergence was recorded for six days after chicken feeding by two doses of B. thuringiensis (1.00 and 5.00 mg/ kg).